The Effect Of HR Competence, IEP Innovation And Service Quality On Project Management In Building Project Performance - Tiara Ardhiti Estungkorodewi; Mombang Sihite; Derriawan Derriawan (Eduvest - Journal of Universal Studies, 2021)
The use of Integrated Engineering Procurement (IEP) information technology can allegedly be used to build HR competencies, service quality, project performance and project management to overcome problems of project time delays, costs, and quality/quality of work. The purpose of this study is to identify the effect of HR competence, IEP innovation (integrated engineering procurement), service quality on project management in improving project performance. This research uses a case study in the Situ Bagendit revitalization project run by PT Adhi Karya Tbk. The research method used is quantitative. Quantitative research using SEM PLS. Sampling through purposive sampling method and obtained 117 research units. The results showed that based on SEM analysis stated that the relationship between HR Competence, IEP Innovation and Service Quality was significantly related to project performance. Likewise, the relationship between Project Management and project performance has created a significant positive.